EFFECT OF PREOPERATIVE INFORAMATION ON PAIN AND ANXIETY - Mollaee, E; Jafarpoor, M; Nasyriziba, F; Hosseini, F; Javadi, F (Iran University of Medical Sciences, 2002)
Background : Surgery is one of the pain and anxiety producing methods of treatment which in used in almost all hospitals. It is the responsibilities of medical team and specially nurses to perform any action to reduce it. It seems that preoperative information play an important role in alleviation of pain and anxiety.   Objective : To determine the effect of preoperative information on pain and anxiety reduction.   Design : This was a randomized clinical trial with control group. For the collection of data questionnaire were used for demographic data, Spiel Berger inventory for assessing anxiety and numerical rating scale for pain.   Samples : 80 Patients were selected and assigned randomly to trial and control groups (40 in each group).   Results : There was no significant difference between two groups considering level of pain, but there was a significant difference between two groups considering level of situational anxiety.   Conclusion : Findings supported the importance of preoperative information in minimizing patient's situational anxiety level.